The scope of consumer protection in the banking sector - حسين, اكرم محمد; عبدالرزاق, اسراء صلاح (Journal of Legal Sciences, 2021)
The interest in the consumer and the search for appropriate means to protect it is not recent. The consumer protection has been the focus of legal, judicial and juristic interest, since the middle of the last century, and this interest has resulted in the adoption of many rules that would provide protection to the consumer as the weak party in the contractual relationship .banking laws sought to determine who is the banking consumer covered by protection, as well as  to indentify financial institutions that are committed to providing protection to the banking consumer when providing banking services, also ,the scope of consumer protection requires determining the banking  activities provided by banks in  order to protect the banking consumer from the risks surrounding.